1981
DOI: 10.1111/j.1600-0773.1981.tb00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hydragogue Drugs: Effect of Surfactants on cAMP Levels in the Rat Jejunal Mucosa in Short Time Experiments in Vivo

Abstract: Theophylline and the surface active agents specified below were instilled into the jejunum of anaesthetized rats, and the cAMP levels in the mucosal tissue determined after 7 1/2 and 15 min. incubation in vivo. Most experiments were done in rats prepared with two tied intestinal loops; one of these served as the control loop and the other as the stimulated loop. The surfactants (mmol/l) included dodecylsulphate (17), dioctylsulphosuccinate (5.6), cetrimonium bromide (4.1), deoxycholic acid (2.4 and 3.6) and Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…According to current view, elevated CAMP levels cause luminal water and electrolyte accumulation because of stimulation of cellular anionic efflux or inhibition of coupled sodium-chloride influx. However, an own study (Sund & Hillestad 1981) failed to demonstrate any increased formation of cAMP by DOSS in the rat jejunum under conditions where the drug significantly alters normal mucosal transport. Since, on the other hand, a substantial rise in cAMP by theophylline was demonstrated, the study suggested that theophylline but not DOSS under these conditions might cause transport alterations mediated via CAMP.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…According to current view, elevated CAMP levels cause luminal water and electrolyte accumulation because of stimulation of cellular anionic efflux or inhibition of coupled sodium-chloride influx. However, an own study (Sund & Hillestad 1981) failed to demonstrate any increased formation of cAMP by DOSS in the rat jejunum under conditions where the drug significantly alters normal mucosal transport. Since, on the other hand, a substantial rise in cAMP by theophylline was demonstrated, the study suggested that theophylline but not DOSS under these conditions might cause transport alterations mediated via CAMP.…”
mentioning
confidence: 93%
“…In the present work, these two possibilities have been explored by studying the influence of theophylline and DOSS on the abovementioned absorption processes in vivo. Another anionic surfactant, dodecylsulphate (=DDS), was also included, since this drug may induce some increased formation of CAMP (Briseid et al 1976(Briseid et al & 1977Sund & Hillestad 1981). A short account of this study has been presented elsewhere (Sund & Olsen 1978).…”
mentioning
confidence: 99%